Survei dan Identifikasi Faktor Awareness Mahasiswa IPB Terhadap Perilaku Pelecehan Seksual dan Kekerasan Menggunakan Regresi Logistik Biner - Ibrahim Arif Muhammad; Rahma Anisa; Mohammad Masjkur (Department of Statistics, IPB, 2022)
The lack of public awareness of sexual harassment as well as physical and verbal abuse are still occurring frequently and becoming a concern in everyday life, especially for women. Sexual harassment is an unwanted behavior or attention from a perpetrator with sexual intentions that disturbs the victim(s). Abuse is a form of one person's action against another party that results in pain and changes both physically and psychologically. The purpose of this study is identifying the number of IPB University students that are aware on the act of sexual harassment and abuse, identifying factors that can affect awareness about it using binary logistic regression, and providing recommendations on how to increase the awareness of it. Majority of the respondents have awareness on both the act of sexual harassment and abuse, whether they have done it or not. In the logistic regression, gender and financial background of the respondents were significant factors of awareness in the act of sexual harassment, whereas in awareness of the abusive behavior, the respondents’ gender, hometown, the time amount of social media usage per day, financial background, and experience of being a victim of it factor significantly. Majority of the respondents suggest that education from various sources should be improved in order to raise awareness to the public.